THE RELEVANCE OF EDUCATIONAL ROBOTICS AS A TEACHING TOOL AND GENDER DIVERSITY IN THIS CONTEXT - Flores de Prá, Julyana; Soares, Nathalia Maria (Revista Interface Tecnológica, 2022)
Educational robotics as a teaching methodology has been presented as a support tool in the development of children and adolescents during the school period. Understanding its transformations, as well as the competitions promoted at this juncture, is relevant given the positive impact that has been observed inside and outside the classroom. Therefore, this study is presented through descriptive research based on literary review and the application of a questionnaire to professionals who work with students who have contact with educational robotics. Seeking to study and highlight the importance of initiatives that encourage the inclusion of experiences with robotics in the process of training elementary and high school students, as well as the relevance and differences observed when there is gender diversity present in this context. Therefore, it can be seen at the end of this article that educational robotics stimulates the development of creativity, logical reasoning and critical thinking. It is also possible to point out that when students have the opportunity to participate in tournaments, they start to show greater commitment, better communication and aptitude for teamwork and tolerance towards others, skills that contribute to the formation of the individual beyond the school environment.